Carbon-coated defect-rich MnFe2O4/MnO heterojunction for high-performance microwave absorption. (July 2022) - Meng, Xun; He, Lin; Liu, Yequn; Yu, Yongsheng; Yang, Weiwei
Abstract: Manganese-based heterostructured nanocomposites have attracted extensive attention due to their abundant interfaces and controllable multi-component synergistic absorption mechanisms resulting in excellent microwave absorption properties. However, the development of the dual manganese-containing magnetic/dielectric heterojunctions and the controllable construction of their heterointerfaces and defects still faces great challenges and remains unrealized. Herein, we successfully synthesized carbon-coated MnFe2 O4 /MnO heterojunction nanocomposites with foam-like macroporous structures for high-performance microwave absorption. The optimized absorber with controlling the MnFe2 O4 /MnO heterojunction to reach the maximum amount exhibits the excellent absorption performance: the strongest reflection loss (RL) value can reach −72.1 dB at 10.45 GHz; the widest effective absorption (RL ≤ −10 dB) bandwidth (EAB) is 5.01 GHz (8.39–13.4 GHz) at 2.83 mm; the EABs at different thicknesses (2–3.1 mm) are all above 4 GHz. Despite multiple loss mechanisms, this brilliant performance is determined and dominated by the modulation of heterointerfaces and defect sites. Inspiringly, our inventive in-situ construction of heterointerfaces and defects provides a new perspective for heterojunction engineering to achieve remarkable microwave absorption properties. Graphical abstract: Image 1